Adsorption of Manganese(II) Ions by EDTA-treated Activated Carbons - Ameena Y. Khan; David W. Mazyck (Adsorption Science & Technology)
The adsorption of manganese(II) ions from aqueous solution onto three different granular activated carbons treated with ethylenediamine tetraacetic acid (EDTA) and its sodium salt was investigated. Characterization of the chelate-treated carbons showed that EDTA altered the physical and chemical properties of the sorbents relative to their untreated counterparts. Furthermore, the modified sorbents exhibited a heightened capacity towards the adsorption of Mn(II) ions from aqueous media. Manganese(II) ion removal increased from 0 to 6.5 mg/g for the lignite coal-based sorbent, from 3.5 to 14.7 mg/g for the wood-based sorbent and from 1.3 to 7.9 mg/g for the bituminous coal-based sorbent. The increased removal is attributed, in part, to the creation of Lewis base sites that participate in covalent interactions and hydrolysis reactions.